Gender in Waiting : Men and Women Asylum Seekers in European Reception Facilities - Demarchi, Giorgia; Lenehan, Sara (World Bank, Washington, DC, 2019)
This paper explores how men and women experience their time waiting for a response to applications for international protection, in asylum seekers’ reception centers in Italy and Greece. The experience of waiting in camps can be characterized as one of extended uncertainty, during which women and men live lives in a new environment, with limited physical and social interactions with local communities. Qualitative data collected in early 2017 reveals that these prolonged waits generate various vulnerabilities, some compounding those already caused by trying journeys, which include gender-specific vulnerabilities. In addition, the paper provides an overview of the aspirations men and women asylum seekers hold as they look at the future. These aspirations are informed by pre-existing gender and social norms, but their development appears to be influenced also by the time in waiting. Specifically, aspirations seem constrained for all by the high levels of uncertainty and duration of the legal process, as well as by limited information, and barriers to interactions with local communities. Thus, men and women miss out on opportunities to qualify or broaden their aspirations, as they wait. Taking into account the different challenges and opportunities men and women asylum seekers face may be helpful in devising more targeted and thus effective policies with regards to asylum seekers during this period in waiting.